2012
DOI: 10.1002/mnfr.201100438
|View full text |Cite
|
Sign up to set email alerts
|

Green tea (–)‐epigallocatechin gallate inhibits IGFI and IGFIIstimulation of 3T3‐L1 preadipocyte mitogenesis via the 67‐kDa laminin receptor, but not AMP‐activated protein kinase pathway

Abstract: The results of this study suggest that EGCG mediates anti-IGF-I and anti-IGF-II signals in preadipocyte mitogenesis via the 67LR but not the AMPK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 54 publications
(158 reference statements)
1
30
1
1
Order By: Relevance
“…In more specialized conditions, LAMR has also been shown to interact with the GM‐CSF receptor (Chen et al, ; Ando et al, ), insulin‐like growth factor receptors I and II (Ku et al, ), insulin receptor and insulin receptor substrates (IRS‐1/2/4) (Ku et al, ), the T‐cell specific adaptor protein TSAd (Park et al, ). LAMR also potentially serves as a receptor for both the anti‐angiogenic agent pigment epithelium‐derived factor (PEDF) (Bernard et al, ) and the pro‐survival pro‐angiogenic midkine protein, which may induce nuclear localization of LAMR (Salama et al, ).…”
Section: /67‐kda Laminin Receptor Functionmentioning
confidence: 99%
“…In more specialized conditions, LAMR has also been shown to interact with the GM‐CSF receptor (Chen et al, ; Ando et al, ), insulin‐like growth factor receptors I and II (Ku et al, ), insulin receptor and insulin receptor substrates (IRS‐1/2/4) (Ku et al, ), the T‐cell specific adaptor protein TSAd (Park et al, ). LAMR also potentially serves as a receptor for both the anti‐angiogenic agent pigment epithelium‐derived factor (PEDF) (Bernard et al, ) and the pro‐survival pro‐angiogenic midkine protein, which may induce nuclear localization of LAMR (Salama et al, ).…”
Section: /67‐kda Laminin Receptor Functionmentioning
confidence: 99%
“…For example, plant extracts including polyphenols, resveratrol, curcumin, and proanthocyanidins, have become increasingly popular in the past decades for their anti-adipogenic properties [1,13,14]. It was also reported that herbal medicine was effective as potential therapy for fatty liver disease, diabetes, and metabolic syndrome [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is ubiquitously expressed in mammals and functions as a redox enzyme implicated in mitochondrial ROS generation [19]. The other two isoforms of this family, p46shc and p52shc, have been described as adaptor proteins that can alter mitogen-activated protein kinase and Fos activation upon stimulation with epidermal growth factor and platelet-derived growth factor [20]. p66shc functionally differentiates from these isoforms.…”
Section: Introductionmentioning
confidence: 99%